2013
DOI: 10.1038/cddis.2013.494
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the NF-κB inhibitor A20 as a key regulator for human adipogenesis

Abstract: The zinc-finger protein A20 is a key player in the negative feedback regulation of the nuclear factor kappa-light-chain-enhancer of activated B-cell (NF-κB) pathway in response to multiple stimuli. Tumor necrosis factor alpha (TNFα), a cytokine with pleiotropic effects on cellular proliferation and differentiation, dramatically increases A20 expression in all tissues. As TNFα inhibits adipocyte differentiation, we have determined the contribution of A20 to the adipogenic capacity of human mesenchymal stromal c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 30 publications
2
9
0
Order By: Relevance
“…Here, we found that shA20 MSCs exhibit an enhanced proliferative capacity as has been demonstrated for other immune cells, which is possibly as a result of increased expression of NF-jB-dependent, anti-apoptotic proteins. Dorronsoro et al reported that A20 is a key regulator in human adipogenesis [35]. In this study, we showed that the adipogenic differentiation capacity was dramatically decreased in shA20 C3 MSCs.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Here, we found that shA20 MSCs exhibit an enhanced proliferative capacity as has been demonstrated for other immune cells, which is possibly as a result of increased expression of NF-jB-dependent, anti-apoptotic proteins. Dorronsoro et al reported that A20 is a key regulator in human adipogenesis [35]. In this study, we showed that the adipogenic differentiation capacity was dramatically decreased in shA20 C3 MSCs.…”
Section: Discussionsupporting
confidence: 57%
“…Dorronsoro et al . reported that A20 is a key regulator in human adipogenesis . In this study, we showed that the adipogenic differentiation capacity was dramatically decreased in shA20 C3 MSCs.…”
Section: Discussionsupporting
confidence: 49%
“…Lentivirus encoding shRNA to silence endogenous A20 expression and EGFP were produced by the Viral Vector Platform at Inbiomed Foundation as described previously. 72,73 Purified human CD8 T cells were preactivated 24 hours with CD3/ CD28 magnetics beads prior lentiviral infection, which was performed at a multiplicity of infection of 10 overnight. After, cells were incubated with plated bound anti-CD3 (OKT3) and anti-CD137 (6B4) or mIgG1 mAbs for 48 hours and Bcl-xL expression levels were monitored by flow cytometry.…”
Section: Nf-kb Luciferase Reporter Assaymentioning
confidence: 99%
“…Activation of the NF‐κB/SMAD7 pathway can lead to MSC differentiation deficiency (Wang et al , ). Dorronsoro et al () demonstrated that the presence of TNFAIP3 allows MSCs to differentiate into adipocytes by maintaining NF‐κB signalling at a basal level. Activated NF‐κB inhibits osteogenic differentiation in bone marrow mesenchymal stem cells (Tang et al , ).…”
mentioning
confidence: 99%